Copper-catalyzed multicomponent reaction of β-trifluoromethyl β-diazo esters enabling the synthesis of β-trifluoromethyl N,N-diacyl-β-amino esters - Du, Youlong; Mei, Haibo; Makarem, Ata; Javahershenas, Ramin; Soloshonok, Vadim A.; Han, Jianlin (Beilstein Journal of Organic Chemistry, 2024)
An efficient multicomponent reaction of newly designed β-trifluoromethyl β-diazo esters, acetonitrile, and carboxylic acids via an interrupted esterification process under copper-catalyzed conditions has been developed, which affords various unsymmetrical β-trifluoromethyl N,N-diacyl-β-amino esters in good to excellent yields. The reaction features mild conditions, a wide scope of β-amino esters and carboxylic acids, and also applicability to large-scale synthesis, thus providing an efficient way for the synthesis of β-trifluoromethyl β-diacylamino esters. Furthermore, this reaction represents the first example of a Mumm rearrangement of β-trifluoromethyl β-diazo esters.
Keywords: β-carbonyl diazo; copper catalyst; fluoroalkyl diazo; Mumm rearrangement; unsymmetrical β-diacylamino esters